The perceptions of occupational nurses regarding needle stick injuries for health care workers in the eThekwini district health facility - Gamede, Primrose Sikhona (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--Stellenbosch University, 2012.